Experimental and modelling studies of mortar containing eggshell powder and silica fume - Broneca Sibin (2022)
There have been an increase of Ordinary Portland Cement (OPC) production since it is the primary binder in concrete and mortar. However, its production consumed a lot of energy and caused many environmental problems. Therefore, various efforts have been made to identify alternative materials to replace cement in concrete and mortar. This includes combining two (2) alternative materials to compensate the shortcomings of each them in the properties of concrete and mortar. This research aimed to study the engineering properties of the binary and ternary blended (TB) cement-mortar containing eggshell powder (ESP) and silica fume (SF). The first objective was to study the microstructural, chemical and physical properties of ESP and SF. The results indicated that both materials were suitable to be used as partial OPC replacement. For the second objective, the flowability, compressive strength, flexural strength and hardened density properties of cement-mortar containing ESP and SF were evaluated at 28 days of curing period. The replacement level for the binary blended mortar varies from 0% to 30%. Meanwhile, the combination for the TB mortar was (ESP%:SF%) 5:12, 10:20, 15:15, 20:10 and 25:5. The results showed that the ESP generally had negative effects on the engineering properties of mortar, while the SF significantly improved the engineering properties of mortar. Nevertheless, the combination of both materials in TB mortar provided better performances than the ESP mortar, but lower than SF mortar. Finally, the mix proportion of TB cement-mortar was optimized using Response Surface Methodology based Central Composite Design (RSM-CCD) model. The software used was Design Expert software. The regression analysis showed that both ESP and SF replacement had significant effects on the engineering properties of TB mortar. Meanwhile, the optimum mix design for the maximum strength and density of the TB mortar was as follows: eggshell powder of 5% and silica fume of 18.8%. As a conclusion, this study provides an insight on the engineering properties of ESP and SF as a potential OPC replacement in binary and ternary blended cement-mortar. This is not only reducing the downside effect of OPC usage and production, but also create more sustainable construction materials and help to protect the environment.